Effects of LED light quality and mixing ratio on the morphology, physiology and phytochemical content of green and red pakchoi in hydroponic indoor vertical farming - Kassim, Rosniza (2023)
The global population is expected to reach 10 billion by 2050, with more than 50% of the world population live in cities. Growing urban population necessitates high-quality food as well as food security, resulting in increasing pricing for fresh produce. Hydroponic indoor vertical farming with artificial lighting is one of the latest method for producing high-quality food crops efficiently, particularly in urban settings. LED light is the ideal artificial light choice for vertical farming since it is efficient, long-lasting, and emits less heat. LED light emits a particular wavelength that may influence plant growth and development. Furthermore, the use of LED wavelengths on various crops has shown excellent results in terms of plant quality, production, and nutrition. Understanding the effects of different light wavelengths on the plant development and accumulation of essential nutrients such as antioxidants is crucial for achieving ideal light conditions for the production of high-quality vegetables in hydroponic indoor vertical farming. The purpose of this study is to examine the influence of various LED wavelengths on green and red pakchoi in the hydroponic vertical farm by measuring morphological and physiological responses as well as secondary metabolite accumulation. The research was carried out at the LED Light Research Lab MARDI, Serdang, which is a walk-in growing chamber with controlled environmental conditions. Green and red pakchoi seedlings were exposed to six distinct wavelengths for 40 days as prescribed by the treatment with photoperiod 12-h day/12-h night. The LED light arrays were; White light (W) as a control (the proportions of R, B and G wavelengths were 48%, 17% and 35%), monochromatic red light (100R) (the proportions of R and B wavelengths were 100% and 0%), combination red and blue light (82R12B) (the proportions of R and B wavelengths were 82% and 12%), combination red and blue light (50R50B) (the proportions of R and B wavelengths were 50% and 50%), monochromatic blue light (100B) (the proportions of R and B wavelengths were 0% and 100%), and the combination red, blue and green light (R69B24G7) (the proportions of R, B and G wavelengths were 69%, 24% and 7%). The findings reveal that 82R18B and 69R24B7G are the best light spectrums for green and red pakchoi in terms of morphology, growth, and phytochemical accumulation. The G wavelength is beneficial to enhance the plants' nutritional quality such as vitamin c, vitamin a and phenolic content. Incorporating a small proportion of G wavelength into growth light sources might improve the indoor vertical farming environment without lowering yield, quality, or phytochemical content of green and red pakchoi. G wavelengths were discovered to be equally as crucial for plants as R and B wavelengths. These findings are expected to be a reference and basis for the application of led light formulation in the production of vegetables in plant factories or any controlled-environment planting system with LED light. However, further research is required to understand the best G proportions to include on R and B wavelengths, as well as to assess other variety of potential vegetables that that may be grown in hydroponic indoor vertical farming with LED lights.